Jmenná deklinace fino-sámských jazyků v ugrofinské perspektivě : Vítu Bubeníkovi, pánu všech pádů, k sedmdesátinám - Hofírková, Lucie; Blažek; Václav (2012)
The Fenno-Ugric case system serves as a chrestomathian example of agglutination. Although it is not always apparent in the living languages, their partial reconstructions in the groups confirm this structure. The present contribution analyzes in details the Fenno-Saamic nominal declension which is further compared with the case systems of other groups of the Fenno-Ugric and Samoyedic languages and finally the Uralic protosystem is reconstructed. The present analysis demonstrates the closer relationship of the Mordvinian case system to Fenno-Saamic than to Mari.